Logging identification and distribution characteristics of high-gamma sandstones in the 7th member of Triassic Yanchang Formation, Ordos Basin - Fuliang YOU; Guangdi LIU; Mingliang SUN; Chaozheng LI; Xiangbai LIU; Cheng AN; Zixin WANG; Yishu LI (Shiyou shiyan dizhi, 2023)
A large number of sandstone interlayers were developed in the shale strata of the 7th member of the Triassic Yanchang Formation (Chang 7 member) in the Ordos Basin. These sandstone interlayers are frequently accompanied by abnormally high natural gamma values as high as 330.5 API. As a result, they are undistingui shable from shale on well profile. To characterize the high-gamma sandstones, the clastic rocks of the Chang 7 member were classified into fine sandstone, siltstone, argillaceous siltstone, silty mudstone, mudstone and shale according to grain size and structural characteristics. Conventional logging data were recalculated and combined into two new parameters—A and B. The new intersection chart composed of parameters A and B and natural gamma logging data can effectively distinguish and identify normal sandstone and high-gamma sandstone in the Chang 7 member. The plane distribution of cumulative thickness of high-gamma sandstone in the Chang 7 member shows that the high-gamma sandstone is mainly located in the southwest of the study area. The finger-like distribution of high-gamma sandstone from the edge to the center of the lake basin indicates that its formation may be related to the volcanic eruption during sedimentary period.